Japan’s environmental politics and governance: from trading nation to ecoNation - Takao, Yasuo (Routledge, 2016)
This book is about the future shape of globalized environmental policy and governance-which is much discussed but little understood. Environmental problems stretch across scales of geographic space and require action at multiple levels of jurisdiction, such as individual level, community level, national level, and global level. Multi-level governance and cross-scale coordination will open up opportunities for a variety of stakeholders to participate in decision-making.